Exploring the efficacy of Transcutaneous Auricular Vagus nerve stimulation (taVNS) in modulating local and systemic inflammation in experimental models of colitis - Fatemeh Hesampour; Diane M Tshikudi; Charles N Bernstein; Jean-Eric Ghia (Bioelectronic Medicine)
Abstract Background Current inflammatory bowel disease (IBD) treatments often fail to achieve lasting remission and have adverse effects. Vagus nerve stimulation (VNS) offers a promising therapy due to its anti-inflammatory effects. Its invasive nature, however, has led to the development of non-invasive methods like transcutaneous auricular VNS (taVNS). This study assesses taVNS’s impact on acute colitis progression, inflammatory, anti-inflammatory, and apoptosis-related markers. Methods Male C57BL/6 mice (11–12 weeks) were used for dextran sulfate sodium (DSS)- and dinitrobenzene sulfonic acid (DNBS)-induced colitis studies. The administration of taVNS or no stimulation (anesthesia without stimulation) for 10 min per mouse began one day before colitis induction and continued daily until sacrifice. Ulcerative colitis (UC)-like colitis was induced by administering 5% DSS in drinking water for 5 days, after which the mice were sacrificed. Crohn’s disease (CD)-like colitis was induced through a single intrarectal injection of DNBS/ethanol, with the mice sacrificed after 3 days. Disease activity index (DAI), macroscopic evaluations, and histological damage were assessed. Colon, spleen, and blood samples were analyzed via qRT-PCR and ELISA. One-way or two-way ANOVA with Bonferroni and Šídák tests were applied. Results taVNS improved DAI, macroscopic, and histological scores in DSS colitis mice, but only partially mitigated weight loss and DAI in DNBS colitis mice. In DSS colitis, taVNS locally decreased colonic inflammation by downregulating pro-inflammatory markers (IL-1β, TNF-α, Mip1β, MMP 9, MMP 2, and Nos2) at the mRNA level and upregulating anti-inflammatory TGF-β in non-colitic conditions at both mRNA and protein levels and IL-10 mRNA levels in both non-colitic and colitic conditions. Systemically, taVNS decreased splenic TNF-α in non-colitic mice and increased serum levels of TGF-β in colitic mice and splenic levels in non-colitic and colitic mice. Effects were absent in DNBS-induced colitis. Additionally, taVNS decreased pro-apoptotic markers (Bax, Bak1, and caspase 8) in non-colitic and colitic conditions and increased the pro-survival molecule Bad in non-colitic mice. Conclusions This study demonstrates that taVNS has model-dependent local and systemic effects, reducing inflammation and apoptosis in UC-like colitis while offering protective benefits in non-colitic conditions. These findings encourage further research into underlying mechanisms and developing adjunct therapies for UC.